(untitled) (Web of Teachers: Inderscience Research, 2024)
This article examines the strategies for fostering cognitive culture among high school students in academic lyceums and vocational schools during chemistry lessons. It highlights the importance of cognitive culture in enhancing students’ understanding, critical thinking, and problem-solving skills. The study analyzes various teaching methods, the role of interactive learning, and the effectiveness of practical tasks. The findings reveal that structured, student-centered approaches significantly contribute to cognitive growth, preparing students for future academic and professional pursuits.